THE SIGNIFICANCE OF THE WORD “FELLOWSHIP” IN 1 JOHN - Woy, Jones Ted Lauda (Klabat Theological Review; Vol 4 No 1 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i1.1137.26-40, 2024)
The epistle of John begins with a prologue instead of a traditional epistolary opening, linking it to the Gospel and introducing the concept of fellowship (Greek: koinōnia), which encompasses communion, participation, and partnership both with God and among believers. John's intent is to invite readers into the fellowship of the apostles, eyewitnesses to Jesus' life, as seen in 1 John 1:3 and reiterated in 5:13 to assure them of eternal life. This paper argues that fellowship in 1 John is inherently communal, challenging interpretations that view it as individualistic. Keywords : fellowship, communal, participation, partnership.